Os discursos de Getúlio Vargas acerca do mundo rural: perspectivas e práticas (1930-1945) - Comiran, Vitória (2018)
In the research “Getúlio Vargas' speeches about the rural world: perspectives and practices 1930-1945”, we sought to understand how the rural world and the respective socioeconomic policies of the government were addressed during Getúlio Vargas' presidency. To carry out this study, we used as sources seventeen speeches by Vargas that cover the rural world, the Constitution and Agrarian Legislation of the period and three civil lawsuits that took place in the northern region of Rio Grande do Sul. Thus, the common thread that guides this research is the problem of the synchrony of the discursive perspectives and socio-legal practices of the first government of Getúlio Vargas on the rural world, contrasted with the diachrony of the Vargas economic policy with the Constitutions and Agrarian Legislations of the period. When observing the historical importance that the Vargas Era had for Brazilian history, we believe it is relevant to address how the government of a politician with populist ideals and industrial interests turned to the rural world and how this changed Brazil's rural bases in the political sphere. , legal and socioeconomic with regard to the Constitution and Agrarian Legislation of the period.